The economic effect of refugee crises on neighbouring host countries: empirical evidence from Pakistan - Baloch, Amdadullah; Shah, Said Zamin; Mohd Noor, Zaleha; Lacheheb, Miloud (John Wiley & Sons, 2017)
There is a considerable debate in terms of opportunities and challenges about the presence of refugees in the neighbouring host countries. Most of the existing discourse has focused only on their humanitarian and security implications. This article, on the other hand, seeks to uncover this issue through a purely economic lens, focusing on the economic impact of more than three million Afghan refugees in Pakistan. Utilizing data for the period 1979–2014 and the ARDL bounds testing approach, we arrive at few important conclusions. The empirical results indicate that Afghan refugees have a strong negative impact on economic growth in Pakistan. The effect holds in both the short run and the long run, suggesting that the influx of refugees lowers real economic activity in the country. Ultimately, the study implies that hosting refugees can never be a boon to Pakistan's economy.